2019
DOI: 10.14295/2238-6416.v73i4.681
|View full text |Cite
|
Sign up to set email alerts
|

Iogurte probiótico com polpa de frutas vermelhas: caracterização físico química e microbiológica, aceitabilidade sensorial e viabilidade dos probióticos

Abstract: Este trabalho teve como objetivo elaborar um iogurte probiótico com polpa de frutas vermelhas (n =3) e avaliar a qualidade microbiológica, a composição físico-química, a viabilidade dos probióticos, a aceitação sensorial e intenção de compra, bem como verificar a viabilidade da cultura probiótica e características físico-químicas (pH, acidez titulável e sinérese) ao longo de 30 dias de estocagem refrigerada. O iogurte apresentou qualidade higiênico sanitária apropriada e composição (média) de: pH de 4,76; acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
6
0
6
Order By: Relevance
“…Other authors also reported an increase in acidity of yogurts with the addition of fruit pulp throughout the storage (GALLINA et al, 2018;BARBOSA;GALLINA, 2017;HOSSAIN et al, 2012). However, the formulations F1 and F2 are considered low-acid products when compared to the traditional yogurts, which must have between 0.6 and 1.5 g lactic acid/100 g, thus they may be a favorable environment for maintaining the viability of probiotic microorganisms.…”
Section: Physicochemical Characterizationmentioning
confidence: 89%
See 2 more Smart Citations
“…Other authors also reported an increase in acidity of yogurts with the addition of fruit pulp throughout the storage (GALLINA et al, 2018;BARBOSA;GALLINA, 2017;HOSSAIN et al, 2012). However, the formulations F1 and F2 are considered low-acid products when compared to the traditional yogurts, which must have between 0.6 and 1.5 g lactic acid/100 g, thus they may be a favorable environment for maintaining the viability of probiotic microorganisms.…”
Section: Physicochemical Characterizationmentioning
confidence: 89%
“…The enumeration of molds and yeasts, coliforms at 30 °C, and coliforms at 45 °C are important parameters for the hygienicsanitary quality of a product (GALLINA et al, 2018). The beverages were analyzed for the presence of microorganisms after 1 day of manufacture, and the results are shown in Table 2.…”
Section: Microbiological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…O valor de acidez também esta próximo aos valores de acidez do iogurte de polpa de abacaxi e mel de O iogurte apresentou teor de proteína (3,69 %) de acordo com o preconizado pela legislação, que prevê um mínimo de 2,9 % de proteína (BRASIL, 2007). O valor protéico esta entre os valores do iogurte de polpa de abacaxi e mel de abelha (2,98 a 4,39 %) citados por Paiva et al (2015) e similar ao valor de iogurte probiótico de frutas vermelhas (3,51 %) obtido por Gallina et al (2018). O iogurte é uma excelente fonte de proteína de alta qualidade, promovendo saciedade (WEBB et al, 2014).…”
Section: Composiçãounclassified
“…Dentre os mais diversos tipos de alimentos funcionais, destacam-se os probióticos, normalmente usados em laticínios, como objetivo de diversos estudos recentes relacionando seus benefícios à saúde (Carvalho et al, 2017;Gallina et al, 2019;Leite et al, 2018;Rolim et al, 2020;Kim et al, 2020;Zendeboodi et al, 2020;Zhou et al, 2020).…”
Section: Introductionunclassified